2020
DOI: 10.31234/osf.io/q9hge
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Task-general efficiency of evidence accumulation as a computationally-defined neurocognitive trait: Implications for clinical neuroscience

Abstract: Quantifying individual differences in higher-order cognitive functions is a foundational area of cognitive science that also has profound implications for research on psychopathology. For the last two decades, the dominant approach in these fields has been to attempt to fractionate higher-order functions into hypothesized components (e.g., “inhibition”, “updating”) through a combination of experimental manipulation and factor analysis. However, the putative structures obtained through this paradigm have recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 143 publications
(167 reference statements)
0
1
0
Order By: Relevance
“…In electrophysiology studies, decisional efficiency has been linked with the build-up rate of the P3b component of the P300 event-related potential (Kelly & O'Connell, 2013), and appears to originate from temporal-parietal activity associated with stimulus detection and attention (Polich, 2007). Interestingly, reduced decisional efficiency is emerging as a neurocognitive risk factor in a range of psychopathologies (for review, see Weigard & Sripada, 2021). A few studies have suggested that decisional efficiency can be increased by catecholamine agonists that modulate brain signal-to-noise ratios (Peters, Vega, Weinstein, Mitchell, & Kayser, 2020;Weigard, Heathcote, & Sripada, 2019), which may be particularly relevant given that brain serotonergic systems have been associated with suicidality (Oquendo et al, 2014;van Heeringen & Mann, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In electrophysiology studies, decisional efficiency has been linked with the build-up rate of the P3b component of the P300 event-related potential (Kelly & O'Connell, 2013), and appears to originate from temporal-parietal activity associated with stimulus detection and attention (Polich, 2007). Interestingly, reduced decisional efficiency is emerging as a neurocognitive risk factor in a range of psychopathologies (for review, see Weigard & Sripada, 2021). A few studies have suggested that decisional efficiency can be increased by catecholamine agonists that modulate brain signal-to-noise ratios (Peters, Vega, Weinstein, Mitchell, & Kayser, 2020;Weigard, Heathcote, & Sripada, 2019), which may be particularly relevant given that brain serotonergic systems have been associated with suicidality (Oquendo et al, 2014;van Heeringen & Mann, 2014).…”
Section: Discussionmentioning
confidence: 99%